Use-value assessment of rural land in the United States - Anderson, John E. (John Edwin), 1951-; England, Richard W. (Lincoln Institute of Land Policy, 2014)
"Explains the origins, key features, and implementation of use-value assessment (UVA) programs in property taxation in the United States during the last half-century. Intended audience consists of academics who study public finance, agricultural and land economics, urban economics and regional planning, and environmental economics; and state tax and conservation. Covers theory, practice, criticism, and reform recommendations"--